2019
DOI: 10.1088/1757-899x/560/1/012148
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fe component from milling yield on characteristics of perlite based geopolymers

Abstract: The mineral and chemical composition of aluminosilicates used in geopolymer systems is critical for optimal structure formation and the overall performance of the geopolymer products. The composition of alumosilicates can be altered during the technological processing, especially, at the stage of fine milling. This study investigated the effect of aluminosilicate contamination with Fe from milling yield, the characteristics of the aluminosilicates with a metal lining, structure formation, and hardened properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The results of XRF analysis demonstrated an elevated concentration of carbon, wherein the case of FA1 and FA2 ash products, those concentrations exceeded the limits regulated by ASTM C618. In previous research studies, the authors of [ 36 , 37 ] reported on the negative impact of unburned carbon as an inert component in a fly ash system, which resulted in poor alkali-activated binder structure formation, and therefore a reduction in strength performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of XRF analysis demonstrated an elevated concentration of carbon, wherein the case of FA1 and FA2 ash products, those concentrations exceeded the limits regulated by ASTM C618. In previous research studies, the authors of [ 36 , 37 ] reported on the negative impact of unburned carbon as an inert component in a fly ash system, which resulted in poor alkali-activated binder structure formation, and therefore a reduction in strength performance.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies [ 36 , 37 ] have shown that the use of milling equipment with metallic lining for dispersion fly ash powders resulted in milling yield in the form of Fe component. When Fe reacts with water during the alkali activation process, it turns into iron hydroxide Fe(OH) 2 with the volume 3–4.5 times larger than that of Fe.…”
Section: Resultsmentioning
confidence: 99%
“…-Aluminosilicate composition of solid phase component with SiO2/ Al2O3 in range of 1.5-2.5; -Concentration of alkaline-earth elements (CaO, MgO) is 10 %, no more; -Vitreous phase content in aluminosilicate component is 50-60 % at least; -Presence of iron, calcium, and inert particles in fly ash [11].…”
Section: Introductionmentioning
confidence: 99%
“…-preparation of an aqueous alkali solution and its subsequent introduction into the aluminosilicate mixture [28] -preliminary exposure of aqueous alkali solution after preparation for 24 hours, followed by adding into the aluminosilicate mixture [29] -activation of alkaline components that presents in aluminosilicate raw materials (exp., perlite) by grinding [11].…”
Section: Introductionmentioning
confidence: 99%